Maurice - Forster, E. M. (Edward Morgan), 1879-1970; Edited by Furbank, P. N. 1920-2014 (London Penguin Books, 2005)
Written during 1913 and 1914, Maurice deals with the then unmentionable subject of homosexuality. More unusual, it concerns a relationship that ends happily.
Include Notes
Keywords: Gay men -- England--Cambridge -- England